2004
DOI: 10.1177/0091270003261899
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Dose, Two‐Way Crossover, Bioequivalence Study of Dexmethylphenidate HCl with and without Food in Healthy Subjects

Abstract: Attention deficit hyperactivity disorder (ADHD) in children is effectively treated by racemic oral methylphenidate (dl-MPH). The d-isomer (d-MPH) has been developed as an improved treatment for ADHD since only half the racemic dose is used. This study, performed in healthy subjects, assessed the effect of food on the pharmacokinetics of dexmethylphenidate hydrochloride (d-MPH HCl) in a single dose (2 x 10-mg tablets), two-way crossover with d-MPH administered to subjects in both a fasting state or after a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This finding is consistent with that of extensive enantiospecific pharmacokinetic studies that have measured both isomers and found the l-isomer to generally attain only a small fraction of that of circulating concentrations of d-MPH (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In addition, the plasma half-life (t 1/2 ) of d-MPH is markedly longer than that of l-MPH. 22 The presystemic metabolism and clearance of d,l-MPH is an enantioselective process resulting in markedly higher plasma concentrations of d-MPH relative to l-MPH.…”
mentioning
confidence: 99%
“…This finding is consistent with that of extensive enantiospecific pharmacokinetic studies that have measured both isomers and found the l-isomer to generally attain only a small fraction of that of circulating concentrations of d-MPH (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In addition, the plasma half-life (t 1/2 ) of d-MPH is markedly longer than that of l-MPH. 22 The presystemic metabolism and clearance of d,l-MPH is an enantioselective process resulting in markedly higher plasma concentrations of d-MPH relative to l-MPH.…”
mentioning
confidence: 99%
“…Second, the study by Quinn et al (2004) dosed the subjects with breakfast; the study by Patrick et al (2013) provided a light breakfast 1 hour before dosing. Food has been reported to delay the d-MPH time to maximum plasma concentration and may increase total MPH exposure (Midha et al, 2001;Teo et al, 2004). Third, the earlier study by Quinn et al (2004) used children with ADHD (n = 32).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Panel A: Data represent model simulated (lines) and observed individual (circles) plasma concentrations of d -MPH after oral dosing with 20 mg MPH (n = 4) [40]; Panel B: Data represent model simulated (line) and observed (circles) plasma concentrations of MPH after two repeated dosing with 10 mg MPH, taken 5 h apart (n = 18) [43]; Panel C: Data represent model simulated (line) and observed (circles) plasma concentrations of d -MPH after oral dosing with 40 mg of MPH (n = 24) [39]; Panel D: Data as described for Panel A obtained after oral dosing with 40 mg MPH (n = 6) [42]; Panel E: Data represent model simulated (lines) and observed plasma concentrations of d -MPH (•) and d -RA(▴) after oral dosing with 20 mg d -MPH (n = 15) [41].…”
Section: Supporting Informationmentioning
confidence: 99%